Blastocystis sp. of Subtypes 2, 4 and 9 in Selected Avian Species, Brazil, 2009-2018 - SYG Marin; CR Silva; JP Andrade; CF Soares; PHC Rodrigues; HCAM Oliveira; DAR Vilela; HLG Coelho; OC Freitas Neto; NRS Martins (Brazilian Journal of Poultry Science)
ABSTRACT Avian species of the metropolitan region of Belo Horizonte, Brazil, submitted to laboratory routine due to a variety of morbid conditions, were diagnosed as carriers of Blastocystis sp. All samples were examined under light microscopy and those with structures suggestive of Blastocystis sp. were tested by PCR. The total DNA was purified from feces and/or intestinal mucosa and used as a template for PCR, targeting the small subunit (SSU) rRNA gene, and the products were sequenced. The sequences detected in two chickens, one passerine (Saltator similis, Thraupidae) and a golden parakeet (Guaruba guarouba, Psittacidae) were phylogenetically characterized and shown to cluster with sequences of subtypes 2, 4 or 9. The occurrence of Blastocystis sp. in domestic and local native avifauna is described and the perspective of a complex local interspecies epidemiology is considered of risk, including to humans.